Computational Issues Associated with Automatic Calculation of Acute Myocardial Infarction Scores. (3rd November 2008) - Destro-Filho Destro-Filho, J. B. J. B.; Machado Machado, S. J. S. S. J. S.; Fonseca Fonseca, G. T. G. T.
Abstract : This paper presents a comparison among the three principal acute myocardial infarction (AMI) scores (Selvester, Aldrich, Anderson-Wilkins) as they are automatically estimated from digital electrocardiographic (ECG) files, in terms of memory occupation and processing time. Theoretical algorithm complexity is also provided. Our simulation study supposes that the ECG signal is already digitized and available within a computer platform. We perform 1000 000 Monte Carlo experiments using the same input files, leading to average results that point out drawbacks and advantages of each score. Since all these calculations do not require either large memory occupation or long processing, automatic estimation is compatible with real-time requirements associated with AMI urgency and with telemedicine systems, being faster than manual calculation, even in the case of simple costless personal microcomputers.